1969
DOI: 10.1159/000130054
|View full text |Cite
|
Sign up to set email alerts
|

The length of secondary chromosomal constrictions in normal individuals and in a nucleolar mutant of <i>Xenopus laevi</i><i>s</i>

Abstract: Secondary chromosomal constrictions are thought to be the loci of the genome which code for ribosomal RNA synthesis. Their metaphase length could depend on nucleolar size or level of functional activity in interphase or on gene content. Wild-type frogs and a frog heterozygous for the Oxford nucleolar mutation were studied to determine which possibility is more probable. The mutant was studied because its single nucleolus is larger than wild-type nucleoli, it has only one constriction, half as many ribosomal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 2 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Rafferty and Sherwin ( 1969) observed a dimorphic secondary constriction in Xenopus laevis. The constriction is probably the NOW, although evidence for this conc%usion was not presented.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rafferty and Sherwin ( 1969) observed a dimorphic secondary constriction in Xenopus laevis. The constriction is probably the NOW, although evidence for this conc%usion was not presented.…”
Section: Discussionmentioning
confidence: 97%
“…Rafferty and Sherwin (1969) found dimorphic secondary constrictions in three of four wild-type frogs and interpreted the dimorphism to result from partial deletions. They suggested that constriction length was a function of DNA content rather than of level of activity or size of nucleolus produced.…”
Section: Discussionmentioning
confidence: 99%
“…C2C12 cells were grown at 37°C in 5% CO 2 . Differentiation media was changed every 24 -48 h. Xenopus A6 cells (Rafferty and Sherwin, 1969) (American Type Culture Collection) were grown at 23°C in L-15 medium plus 15% fetal calf serum.…”
Section: Cell Culture and Library Screenmentioning
confidence: 99%
“…By using a distance-modulated feedback control protocol [15] SICM has achieved sufficient stability to permit real-time monitoring of the membrane dynamics in living epithelial cells over 24 hours [8]. Although it is still not possible to observe directly epithelial cell response to osmotic stress and regeneration in vivo, a well-characterized functional A6 Xenopus laevis renal epithelial cell line [8,16,17] allows study of these processes in vitro without interference from nonepithelial cells. A6 cells grown as a monolayer on membrane filters have Na + transport properties that are similar to mammalian renal distal tubular epithelial cells and have been shown to be a good model for studies of Na + transport regulation [18].…”
mentioning
confidence: 99%